Comprehensive review on cascaded latent heat storage technology: Recent advances and challenges. (30th November 2022) - Shen, Yongliang; Mazhar, Abdur Rehman; Liu, Shuli
Abstract: Cascaded latent heat storage (CLHS) technology has been proven to have advantages in improving the heat transfer rate and heat storage capacity. The objective of this study is to review literature on the CLHS technique to identify research progress, challenges, and future directions. Based on different research methods in the published literature, the key challenges are widely discussed. The different application scenarios of CLHS are summarized and the future research directions are put forward. This review shows that the thermal advantages of CLHS are reflected in different temperature ranges, which can be further enhanced by optimizing the structure of the heat storage unit, the physical properties of the phase change material (PCM), and the boundary conditions. The review also reveals that the main challenges of CLHS technology are the selection, development, and distribution of PCMs. In the future, more accurate intelligent optimization algorithms and dynamic models should be developed for the more complex structures of heat storage units. Reducing overcharging and optimizing PCM volume distribution are considered potential methods to enhance the thermal performance of the CLHS system. Also, more practical applications, especially in the field of low-temperature thermal energy storage and cold storage, should be studied to determine the prospects of CLHS technology through an annual techno-economic evaluation. In addition, a PCM selection procedure and performance evaluation indicator based on "useful energy" is also proposed. Highlights: In-depth discussion of some questions related to CLHS technology A PCMs selection procedure based on the dynamic optimization algorithm is proposed. Performance evaluation indicator based on "useful energy" is recommended. Main challenges and future research directions are put forward.